Fórmulas aproximadas del tipo Lévy-Khintchine - Lobo Segura, Jaime (2001)
The problem of approximation of the characteristic functions defined by a PII in near intervals is studied. We establish some general properties of these functions and of the associated complex matingales, which, with the aid of the decomposition results in [4] and [5], lead to approximate formula of the Lévy-Khintchine type. As a consequence, we obtain the exact law for PII processes in continuous time